(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cheryll Glotfelty’s definition of ecocriticism as “the study of the relationship between literature and the physical environment” has incited the minds of the critics to give a deep thought to the condition of the natural world, constantly under threat due to anthropogenic activities. Activities like deforestation, unreasonable use of natural resources, spreading pollutants in the environment has benefitted man initially but disturbed the ecological equilibrium giving rise to great disasters in the human community. According to William Rueckert, the most glaring problem faced by ecologists is to find grounds upon which both the human and the natural world can coexist and flourish in the same biosphere. Literature plays a vital role in creatingdisseminating bioregional consciousness in human beings. Niranjan Mohanty is quite aware of this fact and his poems provide ample illustrations to this. In this paper I shall take up certain representative poems of Mohanty like “A Subtle Difference”, “A Poem that Never Begins”, Digging, “Kalahandi”, Grief,“The World”, “Prayers to Lord Jagannatha” etc. to discuss Mohanty’s consciousness regarding nature which, if disturbed, threatens the existence of man on earth.